STUDI KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP LOYALITAS KARYAWAN BERDAMPAK PADA KINERJA KARYAWAN - Rina Angesti Widi (UPAJIWA DEWANTARA: Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2018)
Quality and quantity of performance in an organization is influenced by several things such as compensation received by employees, the work environment and the employees’ loyalty. The objectives of the research are to determine effects of compensation, work environment and loyalty on employee performance at PT. LEC, Yogyakarta. The research was a descriptive. The research data was primary data, data collected using questionnaire techniques. The sampling technique was done with probability. Data sources were gathered from employees of PT. LEC. The scale used ordinal scale. Scaling technique used Likert Scale. Instrument test was done by SPSS software. The analysis used descriptive analysis, inferential analysis and path analysis. The analysis used SPSS and SPLS software. The results of the study that compensation, work environment and loyalty simultaneously and significantly affect the performance, but it does not have a significant partial effect. Keywords: Compensation, Work Environment, Loyalty, Performance